Literature along the lines of flight : D.H. Lawrence's later novels and critical theory - Arai, Hidenaga (Costerus ;, 2014)
This book presents new readings of D.H. Lawrence's later novels from the perspective of established critical theory and contemporary thought: a specific critical theory or critical perspective is selected and applied to each novel in order to present particular interpretations of each. Although remaining faithful to one's personal desires without being unduly concerned with the outside world is considered a Lawrentian virtue, I would like to show another Lawrence who was sensitive enough to the outside world and to the social discourses of his time to employ elements of them in his novels, alt.